KAJIAN KOMITMEN ORGANISASI MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 DI KOTA SEMARANG - Sri Kandariyah Nawangsih (Jurnal Riptek, 2019)
The purpose of this research examines the organizational commitment to face the era of the industrial revolution 4.0 in Semarang city and examines the dimensions of organizational commitment in the face of the era of the industrial revolution 4.0 in Semarang city. This research is expected to benefit through research performed on information obtained as input to add insight, integrated and synergistic between one party with the other party, such as a determination of policy, private sector, and academics to achieve the vision and mission of Semarang city in accordance with the targets that have been set. This research is the research libraries by using the method of data collection the library studies against some references including the results of previous research. After the data that is intended to collect and in accordance with the purpose result, then classified and organized for analysis. Results of the study are known to occupy the position of his organizational commitment to each, both as a moderator variable, causes variable, and the result variable. As for the affective commitment involves feeling (emotion-based), continuation commitment appears based on the matter of costs (cost-based reason), and normative commitment appears based on consideration of a sense of obligation to remain in the organization (obligation-based). There is an interesting findings i.e. employees eager maintain jobs is based by a sense of need work, age has a positive influence but not significant toward affective commitment, while salary satisfaction having a positive influence and significantly to affective commitment.